2020
DOI: 10.1186/s12933-020-01166-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk for cardiovascular disease associated with metabolic syndrome and its components: a 13-year prospective study in the RIVANA cohort

Abstract: Background We aimed to investigate the association of metabolic syndrome (MetS) and its single components with cardiovascular risk and estimated their impact on the prematurity of occurrence of cardiovascular events using rate advancement periods (RAPs). Methods We performed prospective analyses among 3976 participants (age range: 35–84, 55% female) in the Vascular Risk in Navarre (RIVANA) Study, a Mediterranean population-based cohort. MetS was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 51 publications
4
103
0
4
Order By: Relevance
“…It is suggested that MetS is an important risk factor for CVD incidence and mortality, as well as all‐cause mortality 47,48 . The present study found a positive association between high DAL (NEAP score) with MetS.…”
Section: Discussionsupporting
confidence: 63%
“…It is suggested that MetS is an important risk factor for CVD incidence and mortality, as well as all‐cause mortality 47,48 . The present study found a positive association between high DAL (NEAP score) with MetS.…”
Section: Discussionsupporting
confidence: 63%
“…From the National Health and Nutrition Examination Survey data, more than a fth of U.S. adults met the criterion of MetS [12] and its prevalence is projected to still increase following the increasing proportion of central obesity and aging population [13,14]. Moreover, large amounts of evidence showed that MetS and its components signi cantly increased the risk of single cardiometabolic diseases and mortality from cardiovascular diseases [15][16][17][18]. These ndings may suggest that MetS could in uence the development of cardiometabolic multimorbidity, but to date, no studies have examined whether and the extent to which MetS and its components are associated with cardiometabolic multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical studies have consistently demonstrated a significant association between MetS and incidence of ischemic stroke [ 2 , 6 , 23 ]. However, the relationship between MetS and the morphological characteristics of carotid plaque instability remains uncertain.…”
Section: Introductionmentioning
confidence: 99%